Settlement of land disputes over ownership in Indonesia land Registration System - Dharsana, I Made Pria; Asriwijaya, Desak Rai Kutha; Kresnadjaja, Indrasari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The Basic Agrarian Law (UUPA) is Law Number 5 of 1960 concerning Basic Agrarian Regulations aimed at resolving the dualism conflict of agrarian law in Indonesia at that time, where previously most of the Indonesian people still applied agrarian law based on Western law colonial and a small part based on customary law. The purpose of writing this journal is to analyze and understand the occurrence of legal disputes against dual certificate holders and to analyze and understand the obstacles and solutions to the resolution of dual certificate legal disputes. The research method used in this paper is a qualitative research method with a normative juridical approach. Based on the results of the study, show that the occurrence of multiple certificates is caused by several factors, namely the existence of bad faith from the certificate applicant, an error on the part of the Land Office, namely in terms of collecting and processing physical data and land juridical data, the unavailability of a comprehensive land registration map, and because the domicile of the interested party is outside the city. Settlement of land disputes can be resolved by way of deliberation by the parties and through the judiciary. On the other hand, there is a need for special procedural law provisions either through deliberation or mediation at the BPN and the courts in the event of a dispute resolution through litigation